Impact of the COVID-19 pandemic on a respiratory physiology department and the patient's perception of rapid service change. Issue 3 (21st January 2022) - Cliff, Ian; Mustfa, Naveed; Hussain, Imran; Munro, Emma; Bishop, Hayley; Stone, Helen
Abstract : Background: Originating as a cluster of unexplained cases of pneumonia in Wuhan, China, a novel coronavirus disease, officially named as COVID-19 by WHO, has now reached a pandemic level. In the wake of this global health crisis, stringent public health measures were implemented to curtail the spread of COVID-19. At a local level, the University Hospitals of North Midlands National Health Service Trust suspended all elective and outpatient activity, primarily to address the current potential implications of the COVID-19 outbreak. Within respiratory physiology, all but urgent and emergency work was suspended. Methods: In June 2020, the service commenced its restoration/recovery plan, which was based on national and international guidelines to ensure safe practice for patients and staff alike. The plan was a roadmap developed to upscale the respiratory physiology service to deliver urgent and routine care and to assist the service to undertake the essential task of managing the patient backlog as a consequence of the interruption of service. Patient concerns and anxieties due to the pandemic was a key aspect of the restoration/recovery plan. The service developed numerous initiatives along with a questionnaire to assess patient experience following attendance for investigations or assessment. Results: The questionnaire confirmed that the initiatives put in place as part of the restoration/recovery plan achieve high levels of satisfaction in terms of communication, interaction within the service, professionalism and importantly patient safety. Conclusion: COVID-19 had a significant impact on routine clinical care and out-patient activity. This brought about significant change in service delivery that required a strict regimen to ensure COVID-19 free status and minimise cross-contamination of service users. The systems and processes introduced demonstrated positive responses and confirmed the objective of patient safety, which translated to the service users.